Ferramentas digitais para aprendizagem colaborativa nos cursos de qualificação profissional da Polícia Militar do Tocantins - Carneiro, Leonardo de Andrade (Universidade Federal do Tocantins, 2020)
This dissertation aims to propose the implementation of digital collaborative learning tools in the Tocantins Military Police in professional qualification courses, demonstrating that collaborative learning can strengthen and develop skills as a requirement for the development and sharing of knowledge as a strategic learning tool resulting from participant interactions. Thus, with a bibliographic review with the publication of three articles and a book chapter respectively: A Critical Analysis on Learning: Collaborative and Ubiquitous Mobile"; "A study on Digital Collaborative Learning Tools"; "A study on Technology-Mediated Learning" and "collaborative learning and its interfaces in technology-mediated learning." Therefore, learning tools must combine theory and practice, space and time, defining strategies as essential factors for more autonomous and dynamic learning, favoring multiple teaching paths. With the publication of the article "Qualification of the Military Police Tocantinense in the face of technology-mediated education" that aimed to know the profile and difficulties and whether this modality of teaching can add necessary knowledge for the end activities of the Military Police Officer. The publication of the article "Collaborative Learning in the Military Police of Tocantins: perspective without frontier", presents the advantages of Chamilo as a learning platform of the Military Police and its feasibility as a learning tool Collaborative. The results show that technology-mediated learning provides shared training, improving the capacities of professionals and building knowledge in the interaction between subjects, and students can produce knowledge guiding their practices in daily life and their qualification without absent from the municipalities for long periods.